Operasi Bedah Plastik Dalam Perspektif Hukum Islam - Prala Ney; Nur Mohamad Kasim; Waode Mustika (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The aim to be achieved in the preparation of this research is to find out the views of Islamic Law regarding the Practice of Plastic Surgery and to know the Legal Impact of Plastic Surgery. This type of research is normative legal research. This normative legal research is research on norms that carry out norms on a building system of norms which is meant regarding standards, standards of applicable rules of choice of courts, understandings and conventions (lessons). legitimate. The results of the research show (1) The practice of plastic surgery according to Islamic law is permissible or lawful because there is a health reason that disturbs someone so that it is necessary to make improvements to the body in order to eliminate pain or harm which of course is not allowed plastic surgery is intended to change sex and change parts of the human body to make it look more beautiful. (2) The legal impact on the practice of plastic surgery can be directly or indirectly. It can be seen directly from a health perspective, and indirectly people who have had plastic surgery can avoid taxes, deceive airport security or immigration officers, manipulate data. Conclusions The practice of plastic surgery according to Islamic law is permissible or lawful.